Scale decisions can reverse conclusions on community assembly processes - Tamara Münkemüller; Laure Gallien; Sébastien Lavergne; Julien Renaud; Cristina Roquet; Sylvain Abdulhak; Stefan Dullinger; Luc Garraud; Antoine Guisan; Jonathan Lenoir; Jens‐Christian Svenning; Jérémie Van Es; et al. (Global Ecology and Biogeography, 2014)
Aim Phylogenetic diversity patterns are increasingly being used to better understand the role of ecological and evolutionary processes in community assembly. Here, we quantify how these patterns are influenced by scale choices in terms of spatial and environmental extent and organismic scales. Location E uropean A lps. Methods We applied 42 sampling strategies differing in their combination of focal scales. For each resulting sub‐dataset, we estimated the phylogenetic diversity of the species pools, phylogenetic α‐diversities of local communities, and statistics commonly used together with null models in order to infer non‐random diversity patterns (i.e. phylogenetic clustering versus over‐dispersion). Finally, we studied the effects of scale choices on these measures using regression analyses. Results Scale choices were decisive for revealing signals in diversity patterns. Notably, changes in focal scales sometimes reversed a pattern of over‐dispersion into clustering. Organismic scale had a stronger effect than spatial and environmental extent. However, we did not find general rules for the direction of change from over‐dispersion to clustering with changing scales. Importantly, these scale issues had only a weak influence when focusing on regional diversity patterns that change along abiotic gradients. Main conclusions Our results call for caution when combining phylogenetic data with distributional data to study how and why communities differ from random expectations of phylogenetic relatedness. These analyses seem to be robust when the focus is on relating community diversity patterns to variation in habitat conditions, such as abiotic gradients. However, if the focus is on identifying relevant assembly rules for local communities, the uncertainty arising from a certain scale choice can be immense. In the latter case, it becomes necessary to test whether emerging patterns are robust to alternative scale choices.